Leaf color change and its correlation with pigment content in 10 ornamental crabapple varieties in spring - HAN Wenxue; JIANG Hao; BIAN Jian; YUN Jinhu; SUN Yanyan; ZHANG Wangxiang; PENG Ye (浙江大学学报. 农业与生命科学版)
In order to explore the varieties of ornamental crabapples with color leaves and a long viewing period in spring and the influence of pigment content on the leaf color, 10 ornamental crabapple varieties, Malus ‘Black Jade’, Malus ‘Pink Spires’, Malus ‘Profusion’, Malus ‘Prairifire’, Malus ‘Royal Raindrop’, Malus ‘Roudph’, Malus ‘Show Time’, Malus ‘Big Red’, Malus ‘Perfect Purple’ and Malus ‘Purple Prince’ from North America were selected as the experimental objects. Their leaf color parameters and pigment contents were tested at different developmental stages (prophase of leaf spreading L1, early stage of leaf spreading L2, late stage of leaf spreading L3). The results showed that the change of lightness (L*) in most varieties was relatively stable, while the fluctuations of redness (a*) and yellowness (b*) were large. The a* values of ‘Black Jade’, ‘Pink Spires’, ‘Profusion’, ‘Roudph’, ‘Big Red’, ‘Perfect Purple’, ‘Purple Prince’ varieties showed significant decreases (P＜0.05), and the a* values of ‘Prairifire’, ‘Royal Raindrop’, ‘Show Time’ varieties increased. The overall variation of b* values was consistent and significantly increased (P＜0.05). Combining with the leaf color map, the a* value can be used as the main indicator for the spring leaf enjoyment of the ornamental crabapple; and the b* value is the auxiliary indicator for the leaf color change of the ornamental crabapple. The contents of chlorophyll and carotenoid increased and the anthocyanin content decreased with the developmental periods, while the content of chlorophyll was always higher than the contents of the other two pigments. Correlation analysis showed that, the anthocyanin contents of 10 ornamental crabapple varieties had significant or extremely significantly positive correlations with the a* values. There was a significant positive correlation between carotenoid content and the b* value of the leaves, and the correlation between chlorophyll content and leaf color parameters varied from variety to variety. In conclusion, among the 10 ornamental crabapple varieties, ‘Prairifire’, ‘Royal Raindrop’, and ‘Show Time’ have higher ornamental value, worthy of development and utilization as red leaf tree species in spring, as the leaves remain red for a long time (about 35 d) in the three developmental stages.